2015
DOI: 10.1007/s00439-015-1605-y
|View full text |Cite
|
Sign up to set email alerts
|

Complex inheritance of ABCA4 disease: four mutations in a family with multiple macular phenotypes

Abstract: Over 800 mutations in the ABCA4 gene cause autosomal recessive Stargardt disease. Due to extensive genetic heterogeneity, observed variant-associated phenotypes can manifest tremendous variability of expression. Furthermore, the high carrier frequency of pathogenic ABCA4 alleles in the general population (~1:20) often results in pseudo-dominant inheritance patterns further complicating the diagnosis and characterization of affected individuals. This study describes a genotype/phenotype analysis of an unusual f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…36 The sibling pair Patient 11 and Patient 12 harbored a deep intronic variant, c.4539+2028C>T, and a deletion/insertion, c.6148–698_c.6670del/insTGTGCACCTCCCTAG, described in a previous report. 37 Patient 5 harbors another deep intronic variant, c.4539+2001G>A.…”
Section: Resultsmentioning
confidence: 99%
“…36 The sibling pair Patient 11 and Patient 12 harbored a deep intronic variant, c.4539+2028C>T, and a deletion/insertion, c.6148–698_c.6670del/insTGTGCACCTCCCTAG, described in a previous report. 37 Patient 5 harbors another deep intronic variant, c.4539+2001G>A.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 67 patients in this group, nine came from families showing a clear pseudo-dominant pattern, either with full or incomplete penetrance (Figure 1). Pseudo-dominance in this gene has been reported many times [6,31,32]. This plays a crucial role, especially in cases where clinical phenotype cannot be easily determined.…”
Section: Discussionmentioning
confidence: 98%
“…Substantial progress has been made with respect to both objectives: several deep intronic ABCA4 variants have been proven to affect splicing8 14 and preliminary data (not shown) indicate that such is also true of rare variants affecting ABCA4 expression. We have also shown that large CNVs, which elude detection by sequencing, are exceptionally rare in the ABCA4 locus and, as a result, account for only a small fraction of ‘missing’ alleles 15. WES of patients with 0 ABCA4 mutations has uncovered causal genes in ~70% of cases with ABCA4 -like phenotypes, including known retinal disease genes ( CRB1, CRX , etc)11 13 and new genes ( RAB28, RDH11 ) 10 12.…”
Section: Introductionmentioning
confidence: 94%